ENDOTHELIAL DYSFUNCTION IS ALREADY PRESENT IN THE PRE-IMPAIRED GLUCOSE TOLERANCE (PRE-IGT) STAGE WITH NO SIGNIFICANT IDENTIFIABLE CARDIOVASCULAR RISK FACTORS - Salmon, Jeannine Ann; Magbuhat, Ann Lorraine; Guerrero-Sali, Ruby Jane; Purino, Francis; Macindo, John Rey; Mercado-Asis, Leilani (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Hyperinsulinemia, which is observed at the pre-impaired glucose tolerance (pre-IGT) stage, is the earliest dysmetabolic signal in the course of type 2 diabetes mellitus. The increased C-peptide during this period has been demonstrated to be the culprit for the development of cardiovascular disease. This study aims to determine the prevalence of endothelial dysfunction among individuals with pre-IGT and to determine the cardiovascular risk factors contributory to the development of endothelial dysfunction. METHODOLOGY We screened adult patients at risk for diabetes mellitus (first-degree relative with type 2 DM, obesity, history of gestational diabetes, and polycystic ovary syndrome). Pertinent demographic, clinical, and laboratory results were determined and recorded. To test for endothelial dysfunction, brachial artery flow-mediated dilatation (FMD) was performed on pre-IGT patients. Binary logistic regression was used to determine significant risk factors affecting endothelial dysfunction and to compare risk factors between FMD (+) and FMD (-) patients. RESULTS Of the 67 patients screened, 41 have pre-IGT with a prevalence of 61%. Among the pre-IGT who had FMD done (31/41), seven were FMD (+) with a prevalence of 22.58%. FMD (+) patients were more obese and had higher total cholesterol and LDL, however, the finding was not statistically significant. Other CVD risk factors were comparable between groups. In addition, none of the risk factors significantly predicted the development of endo- thelial dysfunction among patients with pre-IGT (p>0.05). CONCLUSION At the pre-IGT stage, endothelial dysfunction is already present in 22% of patients. No significant identifiable CVD risk factors have been found so far.